'A sad story of delay and obstructionism': the impact of external relationships on the resourcing and development of Bletchley Park during the Second World War. Issue 3 (16th April 2022) - Cheetham, Thomas
ABSTRACT: Substantial historical attention has been focussed on Bletchley Park's internal organisation and the often-fraught disputes over control of the work and its intelligence products; however, the importance of external inter-departmental relations for the resourcing and development of the signals intelligence agency has sometimes been overlooked or underestimated. This article identifies several ways in which the operation was shaped and sometimes constrained by the compromises the Bletchley Park authorities had to reach with outside organisations to secure the resources they needed. It argues that an accurate picture of Bletchley Park's development must take account of the impacts of these inter-organisational relationships.